L’ateismo come disvalore. Risultati di una verifica empirica - Pérez, Francisco Javier Fiz (Alpha omega, 2010)
The article explores the differences in the values of practising believers, non-practicing believers and atheists. The study was conducted on a group of 1 020 people. The results highlight a very different value structure among the three groups. The principle difference is the fact that believers (both practicing and non-practising) demonstrate a greater degree of benevolence and tolerance, as well as a more traditional (conservative) vision. Atheists generally give a high priority to the values of hedonism and stimulation.